2021
DOI: 10.1007/s00520-021-06018-x
|View full text |Cite
|
Sign up to set email alerts
|

Associated characteristics and treatment outcomes of medication-related osteonecrosis of the jaw in patients receiving denosumab or zoledronic acid for bone metastases

Abstract: Purpose This study aimed to evaluate the association between clinical characteristics and development of medication-related osteonecrosis of the jaw (MRONJ) in patients who underwent dental examinations before the initiation of treatment with denosumab or zoledronic acid, which are bone-modifying agents (BMAs), for bone metastases. Additionally, the clinical outcomes of patients who developed MRONJ were evaluated along with the time to resolution of MRONJ. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 39 publications
5
34
1
Order By: Relevance
“…Moreover, this result was also clearly con rmed by propensity score-matched analysis. The higher risk for developing MRONJ with denosumab than with ZA was consistent with some previous real-world data [40][41][42][43]. Previous randomized controlled trials reported that the incidence of MRONJ in patients treated with denosumab was not signi cantly different from that in patients treated with ZA, although it tended to be higher in the former [25, 27, 32-34, 36, 37].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Moreover, this result was also clearly con rmed by propensity score-matched analysis. The higher risk for developing MRONJ with denosumab than with ZA was consistent with some previous real-world data [40][41][42][43]. Previous randomized controlled trials reported that the incidence of MRONJ in patients treated with denosumab was not signi cantly different from that in patients treated with ZA, although it tended to be higher in the former [25, 27, 32-34, 36, 37].…”
Section: Discussionsupporting
confidence: 88%
“…The incidences of MRONJ in the present study were 9.6% and 4.8% in the denosumab and ZA groups, respectively. The reported incidence of MRONJ is 1-17% [25,27,[29][30][31][32][33][34][35][36][37][38][39][40][41][42], and the incidences of MRONJ in our study were within this range for both groups.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Studies have shown that invasive dental procedures such as tooth extraction are a risk factor for the onset of MRONJ 4 7 , and therefore, tooth extraction tends to be avoided in these patients. The 2014 American Association of Oral and Maxillofacial Surgeons (AAOMS) position paper on medication-related osteonecrosis of the jaw update described that dentoalveolar surgeries such as tooth extraction are considered a major risk factor for developing MRONJ 1 .…”
Section: Introductionmentioning
confidence: 99%